Family Medicine Residency Graduates' Preparation for Quality Improvement Leadership - Lichkus, Jonathan (J Grad Med Educ, 2019)
BACKGROUND: Training in quality improvement (QI) is a standard component of family medicine residency education. Graduating family medicine residents' ability to lead QI initiatives is unknown. OBJECTIVE: We assessed the preparedness of graduating family medicine residents to lead QI projects and to identify factors that may increase such readiness. METHODS: Milestone data for all graduating family medicine residents were linked to a practice demographic questionnaire completed by the same residents who registered for the American Board of Family Medicine certification examination between 2014 and 2017. The change in self-assessed QI preparedness over time and its association with faculty-assigned milestone ratings were examined using descriptive and regression analyses. RESULTS: The questionnaire had a 100% response rate (12 208 responded). Between 2014 and 2017, the percentage of residents who self-reported being “extremely” or “moderately” prepared to lead QI projects increased from 72.7% (2208 of 3038) to 75.8% (2434 of 3210, P = .009). Self-reported QI team leadership was associated with 93% higher odds of feeling extremely prepared compared to moderately prepared (odds ratio 1.93, 95% CI 1.58–2.35). The average midyear faculty-assigned milestone rating for QI among residents who felt “extremely” prepared was 3.28 compared to 3.14 among those who felt “not at all” prepared. CONCLUSIONS: Over the past 4 years, family medicine residents' self-assessed preparedness to lead QI projects has barely increased. There was no correlation between self-assessed preparation and faculty-assigned milestone rating. However, we found a small association between self-reported QI leadership and self-assessed QI preparedness.